An Empirical Analysis of the Role of Technology and Digitisation in Entrepreneurial Success - Giriraj Kiradoo (Research Aspects in Arts and Social Studies Vol. 8, 2023)
This research explored the impact of technology and digitisation on entrepreneurial success by analysing the responses of 150 new entrepreneurs. The dependent variable of entrepreneurial success was operationalised, and the independent variables included technology adoption level, digitisation level, business experience, education level and financial capital. The survey results, conducted using SPSS software, indicated that technology adoption, digitisation, business experience, education, and financial capital are all linked to entrepreneurial success. Technology adoption level and digitisation level had the strongest associations. This study provides new insight into how technology and digitisation can create successful businesses. The implications of the findings suggest that entrepreneurs should focus on these factors to increase their chances of success.